Junior high school students’ abilities in solving the open-ended mathematical problems with the context of Songket motif - Jeri Araiku; Elika Kurniadi; Weni Dwi Pratiwi (Jurnal Elemen, 2022)
Many researchers stated that most students struggle to solve higher mathematical problems, including open-ended problems. One of many solutions is to apply a realistic context close to students. Hence, this research aimed to analyze students’ abilities in solving an open-ended mathematical problem using the Songket context, particularly the Kembang Tengah motif. The subjects were 24 seventh graders. The instruments for this descriptive research were an open-ended problem and an interview sheet. The results show that in solving the open-ended problem, 88.33% of students understood the problem, 59.72% were able to construct, and 72.22% applied the plan, while 52.78% wrote the conclusion. No students evaluated their solution to the problem. In implementing open-ended problems in the traditional context, students have different solutions based on their various experiences with the context, problem-solving schema, and mean-putting on the problem. They also applied multiple problem-solving strategies in working the problem. The similarity was the use of assumptions in solving the problem. However, some assumptions were inconsistent, neither their prior work nor other mathematical concepts. Therefore, teachers and researchers need to emphasize students’ written self-evaluation to check and improve their solutions. Another suggestion is to see the metacognitive process in solving the open-ended mathematical problem using a specific tradition. Furthermore, teachers should engage more in using open-ended problems and scaffold students when facing obstacles in solving them.